Ferroelectric switching behavior of nanoscale Hf0.5Zr0.5O2 grains. (15th December 2021) - Chen, Qiang; Zhang, Yuke; Liu, Wenyan; Jiang, Jie; Yang, Qiong; Jiang, Limei
Highlights: PFM shows that HZO grain's domain switching ability increases as its size dicreases. DFT reveal that surface energy of f -phase grain is lower than that of m -phase grain. Multi-phase coexistence phase field model is developed to study grain size effect. oriented f -phase is most stable and has largest volume as grain size reduces. Abstract: Grain size has shown significant effect on the ferroelectricity of HfO2 -based thin films. However, its microscopic mechanism remains unclear. For this purpose, Hf0.5 Zr0.5 O2 film with different sized grains was prepared by radio frequency magnetron sputtering. The piezoresponse force microscope characterization of the domain switching properties of nanograins shows that domain switching ability of the grain becomes better as its size decreases within the size range we studied. Then, density functional theory (DFT) calculation of grains' energy proves that the lower surface energy of ferroelectric phase is the key factor to make the ferroelectric phase more stable and larger proportion in smaller sized grain. Finally, a multi-phase coexistence phase field model is developed based on the DFT calculation. It is found out that if the contribution of surface energy to the total energy of nano-grain increases, the volume fraction of ferroelectric phase will increase. And (001) ferroelectric phase with the lowest surface energy density will be the most stable and account for the largest volume fraction. Our finding provides a microscopic insight into the "grain size effect" and also some guidelines for high-performance ferroelectric thin films preparation through "grain size engineering". Graphical abstract: Ferroelectric switching behavior of nanoscale Hf0.5 Zr0.5 O2 grains Image, graphical abstract